Vibration Measurement and Analysis Using Heterodyne Laser Detection - Hussain, Mohammed A.; MohamedSalih, Hussam M. A. (Nahrain University College of Engineering Journal, 2007)
An experimental Michelson interferometer arrangement has been implemented utilizing the principle of laser Doppler vibrometry. He-Ne laser has been used as a coherent light source. The circuit for heterodyne detection has been built to detect and record Doppler signals. Two types of materials have been used as vibrating panel, which are excited by acoustic waves applied from a loudspeaker connected to a function generator. The applied waves were in frequency range of 10- 100Hz. The recorded results of the experimental work demonstrate that the vibration frequency of the panel conforms to the applied frequency when the ratio between the applied and natural frequencies is greater than two (or less than one half).